THE INFLUENCE OF ACCOUNTING KNOWLEDGE AND BUSINESS EXPERIENCE ON THE PERCEPTION OF ACCOUNTING INFORMATION USE AMONG MICRO-ENTERPRISES AND SMALL IN ULUJADI DISTRICT - Kiki Berlian Sari; Merinda Anisa; Andi Atirah; Jamaluddin; Ernawaty Usman; Ridwan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of accounting knowledge and business experience on the perception of accounting information use among micro and small business owners in Ulujadi District. Micro and small businesses play a vital role in the local economy, but often face challenges in effective financial management. Using a quantitative approach, data were collected through questionnaires distributed to micro and small business owners in the area. Data analysis was conducted using multiple linear regression to test the influence of each independent variable on the dependent variable. The results indicate that both accounting knowledge and business experience have a positive and significant influence on the perception of accounting information use. This finding indicates that increased accounting understanding and accumulated entrepreneurial experience can encourage business owners to utilize accounting information more effectively in business decision-making. This study provides important implications for policymakers and training institutions in designing small business capacity-building programs.